Riesgo Crediticio de la Cooperativa de Ahorro y Crédito “San Antonio” Ltda. La Unión Periodo 2020 2021. - Cárdenas Garzón, Alexander Vidal (2022)
This case study has as its theme: Risk of La Cooperativa de Ahorro y Crédito San Antonio Ltda. La Unión period 2020 2021, La Cooperativa de Ahorro y Crédito San Antonio Ltda. La Unión is an organization whose main functions are to offer financial and consumer credit products such as microcredits that enable its members to access them. It is located on Camilo Ponce and Martha de Roldos streets in the parish of La Unión. The existence of La Cooperativa de Ahorro y Crédito "San Antonio" Ltda. It has the problem of lacking adequate methodological tools that allow the operation on a large scale while accepting credit, as a result, the degree of indebtedness increases. It is necessary to have an effective management strategy to control it. All countries depend on the financial sector to be successful, but Ecuador's credit sector is the most difficult to manage well. This is often the case because the economic revenue sources for payments have not been taxed. Your goal is to employ management strategies that support earned invoice turnover and subsequent debt reduction. Today, maintaining a sophisticated fee control system, adhering to prefunding policies, recognizing risk and implementing an effective risk management strategy are standard operating procedures typical of financial institutions seeking to better control costs.